2014
DOI: 10.1155/2014/949521
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Microcystin-LR inIn VitroandIn VivoExperimental Models

Abstract: Microcystin-LR (MCLR) is a cyanobacterial toxin known for its acute hepatotoxicity. Despite being recognized as tumour promoter, its genotoxicity is far from being completely clarified, particularly in organs other than liver. In this work, we used the comet and/or the micronucleus (MN) assays to study the genotoxicity of MCLR in kidney- (Vero-E6) and liver-derived (HepG2) cell lines and in blood cells from MCLR-exposed mice. MCLR treatment (5 and 20 μM) caused a significant induction in the MN frequency in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Molecular analysis of the TK mutants revealed that MC-LR specifically induced loss of heterozygosity (LOH) at the TK locus, but not point mutations or other small structural changes. Dias et al [84] also reported that MC-LR treatment caused a significant induction of micronuclei in both HepG2 and Vero-E6 cells in vitro. Similarly, a positive effect was also observed in reticulocytes of mice i.p.…”
Section: Genotoxicitymentioning
confidence: 92%
See 1 more Smart Citation
“…Molecular analysis of the TK mutants revealed that MC-LR specifically induced loss of heterozygosity (LOH) at the TK locus, but not point mutations or other small structural changes. Dias et al [84] also reported that MC-LR treatment caused a significant induction of micronuclei in both HepG2 and Vero-E6 cells in vitro. Similarly, a positive effect was also observed in reticulocytes of mice i.p.…”
Section: Genotoxicitymentioning
confidence: 92%
“…MC-LR. Moreover, the fluorescence in situ hybridization (FISH) analysis of the MN content (HepG2 cells) suggested that MC-LR induces both chromosome breaks and loss [84]. Significantly elevated MN frequency was also observed in bone marrow cells of MC-LR-treated mice [85].…”
Section: Genotoxicitymentioning
confidence: 99%
“…The comet length was positively correlated with the level of DNA breakage in cell because the distribution the comet was heterogeneous [19]. The highest value of the markers of DNA damage would be increased with increasing the toxicant dose this may be due to insufficient produce of antioxidant defense systems to scavenge the ROS that is generated by MC-LR which lead to finding their way across nuclear membrane indicating DNA strand breakage [42][43][44][45][46].…”
Section: Dna Damagementioning
confidence: 99%
“…Previous results from the comet assay in mice leukocytes have shown that MC-LR (37.5 μ g/kg bw/day, i.p.) induced a 2-fold transient increase in the level of DNA breaks after 30 min exposure [ 15 ]. In vivo studies by Kujbida et al suggested that topical application of MC-LR (1000 nM) for 4 hours to male rats caused an improvement of the number of rolling and adhered leukocytes in the endothelium of postcapillary mesenteric venules [ 16 ].…”
Section: Role Of Hematological Parameters In Microcystin Mediated mentioning
confidence: 99%